ANALISIS KUALITAS PRODUK ARANG BRIKET PADA KEBUTUHAN PASAR EKSPOR DI TIMUR TENGAH DAN EROPA PADA PT. NUDIRA SUMBER DAYA INDONESIA - Rubby Rahman Tsani; Fikri Muhammad Mauluddin; Ricko Christian Hotlan Tinambunan; Syifa Fajar Maulani, (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This research is entitled “Analysis of the Quality of Briquette Charcoal Products on the Needs of Export Markets in the Middle East and Europe of PT. Nudira Sumber Daya Indonesia). Coconut briquette charcoal is one of Indonesia's leading products that is widely popular in various world markets, limiting research to only the Middle East and European markets. This study was made for prospective exporters with the aim of analyzing the quality of coconut briquette charcoal products in the European and Middle Eastern markets. This study also aims to provide solutions, information to prospective exporters of coconut briquette charcoal to better know what kind of market needs are suitable to penetrate the market in each existing segment. This study uses primary and secondary data with data collection techniques through observation, interviews, and documentation studies. The data analysis method used is descriptive qualitative. The author found several differences in product attributes based on the taste of coconut briquette charcoal in the two markets. The author also suggests that further research into broader markets other than the Middle East and European markets.